Penerapan Teknik Pembelajaran Gallery Walk terhadap Hasil Belajar Sumatif pada Siswa Biologi Kelas XI Fase F - Alda Kaironnisa; Evrialiani Rosba; Erismar Amri (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
This research is motivated by the low student learning outcomes caused by the learning process that is not optimal. The application of discussion methods by teachers is less effective so that interaction and cooperation between students are minimal, resulting in low understanding of the material. The purpose of this study is to determine the effect of the application of the Gallery Walk learning technique on the summative assessment of Biology students of grade XI Phase F at SMAN 2 Lubuk Sikaping. This study uses an experimental method with a Randomized Control Group Posttest Only Design. The study population was all students of grade XI Phase F of SMAN 2 Lubuk Sikaping in the even semester of the 2024/2025 academic year totaling five classes, with a sample of two classes (XIF1 and XIF2) selected using a purposive sampling technique. The research instrument was a multiple-choice question, while data analysis used a t-test. The results showed that the average summative assessment of the experimental class was 78.54 and the control class was 73.73. The t-test produced a t count of 1.86 > t table 1.66, so H1 was accepted. This proves the positive influence of the applied learning techniques. Thus, it can be concluded that the Gallery Walk technique can improve the summative learning outcomes of Biology students of class XI Phase F at SMAN 2 Lubuk Sikaping in the 2024/2025 academic year.